2011
DOI: 10.1007/s00270-011-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of the IVC: Rule Rather Than Exception After Longer Indwelling Times for the Günther Tulip and Celect Retrievable Filters

Abstract: Longer indwelling times usually result in vena caval perforation by retrievable Günther Tulip and Celect IVC filters. Although infrequently reported in the literature, clinical sequelae from IVC filter components breaching the vena cava can be significant. We advocate filter retrieval as early as clinically indicated and increased attention to the appearance of IVC filters on all follow-up imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 25 publications
2
83
0
Order By: Relevance
“…It is likely that asymptomatic perforation of the caval wall occurs with several filter types, and in the absence of a CT scan this is not easy to quantify. Durack et al demonstrated that strut penetration of the caval wall is the rule rather than the exception and also that complications associated with it can be significant [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that asymptomatic perforation of the caval wall occurs with several filter types, and in the absence of a CT scan this is not easy to quantify. Durack et al demonstrated that strut penetration of the caval wall is the rule rather than the exception and also that complications associated with it can be significant [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have demonstrated that penetrations can progress over time, 19,26,28 and the longer the indwelling time is, the further the penetration depth beyond the caval wall is. 26 For symptomatic patients, filter retrieval should be strongly considered because pain related to a filter is often relieved after filter removal.…”
Section: -13mentioning
confidence: 99%
“…However, retrieving these filters should be considered, particularly in cases of penetration already involving adjacent organs or structures, because penetrations are known to progress over time. 19,26,28 Retrieval of optional filters in this setting can be performed safely. 33,34 For cases in which the filter is not removed, follow-up CT scans are appropriate.…”
Section: -13mentioning
confidence: 99%
“…Poor retrieval rates correspond to an increase in reported adverse events 7. Complications associated with VCFs include increased risk of deep vein thrombosis (DVT), inferior vena cava thrombosis, inferior vena cava penetration, VCF fracture, and VCF embolization 7, 9, 10, 11. Given these trends, the US Food and Drug Administration has issued a safety communication highlighting the need to remove VCFs once the risk of pulmonary embolism (PE) has subsided based on modeling studies showing that VCFs are most clinically beneficial if retrieved within 90 days after implantation 11, 12…”
Section: Introductionmentioning
confidence: 99%